THE EXAMINATION OF THE STRENGTH AND AEROBIC EXERCISE ON DOWN SYNDROME PATIENTS - Singh, Balkaran; Kaur, Inderpreet (International Journal of Psychosocial Rehabilitation, 2021)
As a population, people with Down Syndrome (DS) engage in a lower degree of physical activity than those with good development, and they encounter challenges such as medical comorbidity, access issues, and the social perspective of being physically active. As specialists in the exercise of prescription and physical activity, therapists who work with children with developmental disabilities (DS) confront several problems in their work. People who engage in regular physical activity are less likely to suffer from a variety of health conditions. Exercises may be a fun and engaging way to get people to exercise more often while also improving their physical health and motor skills. Cycling, dancing, jogging (long-distance running), swimming, and walking are all examples of activities that can increase cognitive function and aerobic capacity as well as physical strength. Disabled people’s everyday lives depend on them getting enough physical activity and exercise. Accordingly, the purpose of this research is to look at how exercise affects DS’s physical and functional fitness